Implementation of Permendikbudristekdikti Number 40 of 2021 Concerning the Assignment of Teachers as School Principals - Damayanti, Novi; Kristiawan, Muhammad; Nurlina, Nurlina (Yayasan Sembilan Pemuda Indonesia, 2025)
The purpose of this study is to determine (1) the mechanism for recruiting prospective school principals (2) the process of appointing school principals, and (3) efforts to overcome factors inhibiting the implementation of Dikbud Ristek Number 40 of 2021. This study was descriptive qualitative. Research location was Palembang City Education Office and SD Negeri 226 Palembang. Research subjects were Head of GTK Division and Principal. Instrument was the researcher himself. Data collection was observation, interviews, and documentation. Analysis through data reduction, data presentation, and drawing conclusions. Checking the validity of data through triangulation of sources and data collection techniques, results, and conclusions. From the results of the study, it was concluded that the requirements and process for appointing school principals in Palembang City are in accordance with the mandate of Minister of Education and Culture, Research and Technology Regulation (Permendikbudristekdikti) Number 40 of 2021 concerning the Assignment of Teachers as Principals. Efforts to overcome the inhibiting factors inhibiting the implementation of Permendikbudristekdikti Number 40 of 2021 are to always communicate with the central government in the stages of appointing school principals through the Principal Supervisor School (KSPS) application.